2014
DOI: 10.1177/1548051814531825
|View full text |Cite
|
Sign up to set email alerts
|

Board Chair Authentic Leadership and Nonexecutives’ Motivation and Commitment

Abstract: Using data from a sample of 606 nonexecutives sitting on boards of a Canadian credit union, this study tests the relationship between chairs' authentic leadership on boards and nonexecutives' motivation and commitment. Hypothesis validation indicates that chairs with an authentic leadership style favor motivation and commitment through the emergence of a participative safety climate based on transparency and idea sharing. This relationship is stronger when executives perceive a high-quality relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 73 publications
4
19
0
Order By: Relevance
“…However, this argument is contested in recent studies, in which scholars suggested that a separate board chair can facilitate greater collaboration with the CEO and other board members, resulting in a better firm performance (Bezemer et al, 2018; Krause, 2017; Morais, Kakabadse, & Kakabadse, 2020). In fact, the authors found that effective board chairs help alleviate board–CEO conflicts, orient board members to more strongly emphasize shareholders' interests, and engage in productive discussions by facilitating a participatory environment (Bezemer et al, 2018; Guerrero, Lapalme, & Séguin, 2015; Shekshnia, 2018; Veltrop et al, 2020). They influence an organization's capacity to achieve goals and build high morale among employees as a result of their organizational awareness (Bailey & Peck, 2013; Y. D. Harrison & Murray, 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, this argument is contested in recent studies, in which scholars suggested that a separate board chair can facilitate greater collaboration with the CEO and other board members, resulting in a better firm performance (Bezemer et al, 2018; Krause, 2017; Morais, Kakabadse, & Kakabadse, 2020). In fact, the authors found that effective board chairs help alleviate board–CEO conflicts, orient board members to more strongly emphasize shareholders' interests, and engage in productive discussions by facilitating a participatory environment (Bezemer et al, 2018; Guerrero, Lapalme, & Séguin, 2015; Shekshnia, 2018; Veltrop et al, 2020). They influence an organization's capacity to achieve goals and build high morale among employees as a result of their organizational awareness (Bailey & Peck, 2013; Y. D. Harrison & Murray, 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…This shows that although AL only has a minimum impact on people with low motivation, it is a more effective leadership style than authoritarian leadership. Guerrero, Lapalme, and Séguin (2015) hypothesised that a safety climate would mediate the relationship between the chair's AL style and non-executives' pro-organisational motivation.…”
Section: Relationship Between Authentic Leadership and Job Motivationmentioning
confidence: 99%
“…This participative leadership differs from the notion of participative leadership in educational reform studies, which focuses on distributed leadership in schools, as it does not refer to some shared influence in decision-making by a school leader with his or her employees (Somech, 2005). Rather, this supervisory board chair participative leadership refers to a supervisory board chair's openness to all board members' input in the decision-making process by giving them all a chance to voice their opinions and encouraging them to express their ideas (Guerrero et al, 2015). This prevents some members from feeling put off and developing negative feelings towards the group, leading to fault lines, decline in cohesion or detrimental relationship conflicts (Machold et al, 2011).…”
Section: Chair Participative Leadershipmentioning
confidence: 99%